Nutrition Therapy and Pathophysiology Book Only, 4th Edition - Marcia Nelms; Kathryn P. Sucher (Cengage Learning, 2019)
A practical all-in-one resource for students, clinicians and researchers, NUTRITION THERAPY AND PATHOPHYSIOLOGY, 4th Edition, delivers a comprehensive review of disease pathophysiology and treatment that reflects the latest research, evidence-based practice guidelines, and scope and standards of dietetics practice. It clearly connects nutrition therapy practices and expected outcomes to underlying disease processes at every level--from cells to organ systems. Detailed illustrations enhance your understanding of disease progression, surgical procedures and treatment protocols, while end-of-chapter tables describing complementary and alternative therapies provide a quick-reference resource. In addition Practitioner Interviews provide insight for working with patients in real-world practice. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.